Assessment Practice Reconstruction: Addressing the Digital Literacy Challenges of Elementary School Students - Kiki Niken Saputri; Intan Sari Rufiana; Sri Rahayuningsih (Journal of Practice Learning and Educational Development, 2026)
This study aims to critically analyze classroom assessment practices and the factors contributing to the gap between digital multiliteracy assessment demands and actual implementation, as well as to propose adaptive assessment reconstruction directions aligned with student characteristics and twenty-first-century demands. The study employs a qualitative approach with a case study design conducted at SD Negeri I Arjasa Situbondo during the 2025/2026 academic year. Data collection techniques include participatory observation, in-depth interviews, and document analysis. Data analysis follows the stages of data condensation, data display, and conclusion drawing and verification. The findings reveal that assessment practices remain dominated by conventional approaches, specifically written tests in the form of essay and short-answer questions, oriented exclusively toward measuring cognitive learning outcomes. Teachers have not yet implemented diagnostic assessment, structured formative assessment, or varied summative assessment. The use of technology in assessment is entirely absent, while students’ considerable digital literacy potential remains underutilized. Factors contributing to the gap include limited teacher digital competence, insufficient systemic school support, and the unavailability of digital assessment models suited to elementary school student characteristics. This study recommends assessment reconstruction through the systematic development of teacher digital competence, the development of multimodal digital assessment models, the application of adaptive assessment approaches, and the integration of assessment into the learning process.